Association of absolute lymphocyte and cd4 T cell count ratio with outcome of HIV-negative TB meningitis patients- A longitudinal study. - Kumar, Pratyush; Goel, Dr. (Prof) Deepak; Mittal, Manish; Bhatt, Ashwani (Student's Journal of Health Research Africa, 2025)
Background Tuberculous meningitis (TBM), the most severe form of tuberculosis, presents significant diagnostic and therapeutic challenges. Cellular immunity, particularly CD4+ T lymphocytes and absolute lymphocyte count (ALC), plays a critical role in host defense against Mycobacterium tuberculosis. However, the prognostic significance of ALC and CD4 counts in HIV-negative TBM patients remains underexplored in India. Objective: To assess the association between absolute lymphocyte count and CD4 T cell count with clinical outcomes in HIV-negative TBM patients. Methods This was a longitudinal follow-up study conducted in the Department of Neurology, Himalayan Institute of Medical Sciences, Dehradun, over 2 years. A total of 53 HIV-negative adult TBM patients were enrolled and classified by TBM stage (I–III) and diagnostic certainty (definite, probable, possible) using MRC grading and Marais criteria, respectively. Results Among 53 patients, 23 were male and 30 were female. Females had significantly better outcomes (83.3% vs 47.8%, p = 0.006, RR = 2.36). Patients in earlier TBM stages had higher good outcomes: Stage I (85.7%), Stage II (78.7%), Stage III (30.7%) (p = 0.004). No statistically significant association was found between outcome and ALC (p = 0.424) or CD4 count group (p = 0.856), though trends favored better prognosis in patients with normal immune parameters. Duration of dexamethasone therapy and symptom onset also showed no significant impact on outcome. Conclusion While TBM stage and gender were significantly associated with clinical outcome, no definitive link was observed between ALC or CD4 count and prognosis in HIV-negative TBM patients. Further large-scale studies are warranted to validate the prognostic utility of immune markers in TBM. Recommendations To confirm the predictive significance of ALC and CD4 counts in HIV-negative TBM, future research should involve larger, multicenter cohorts.